Management strategies and technology fluidity in the Asian business sector - Ordóñez de Pablos, Patricia 1975- (IGI Global, Disseminator of Knowledge, 2018)
"This book explores the state of the art, emerging topics, challenges and success factors in management and technology in Asia. It shares new theories, research findings, and case studies, to enhance understanding and collaboration in business, management and technology in Asia. It focuses on Asia, with a special attention to South East Asian countries"--
Keywords: Management / Asia; Industrial management / Asia; Technological innovations / Asia / Management